CHEEK TEETH OF LISTRIODON PENTAPOTAMIAE FROM THE LOWER SIWALIK HILLS OF PUNJAB, PAKISTAN - K. Samiullah M. A. Khan; M. Akhtar (Journal of Animal and Plant Sciences, 2010)
New dental material of Listriodon pentapotamiae has been described from the Miocene rocks of Dhok Bun Ameer Khatoon, district Chakwal, Punjab Pakistan. This material consists of an isolated lower left third premolar, an isolated lower right fourth premolar, an isolated lower left first molar and an isolated upper right canine. These specimens provide new data and give additional information on the distribution of species Listriodon pentapotamiae and contribute to recent work on the suids from the Lower Siwalik Hills of Pakistan.
Keywords: Listriodon pentapotamiae; Dhok Bun Ameer Khatoon; Lower Siwaliks; Pakistan